2016
DOI: 10.1021/acs.est.6b02702
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Cu(II) in Catalyzing Hydrolysis and Oxidation of β-Lactam Antibiotics

Abstract: The widely used β-lactam antibiotics such as penicillins and cephalosporins are known to be susceptible to Cu-catalyzed hydrolysis at their four-membered β-lactam ring. However, this study elucidates that Cu can in fact play multiple roles in promoting the hydrolysis and/or oxidation of β-lactam antibiotics under environmental aquatic conditions (pH 5.0-9.0 and 22 °C), depending on β-lactams' structural characteristics and solution pH. Most significantly, the β-lactam antibiotics that contain a phenylglycine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 46 publications
1
57
1
Order By: Relevance
“…The catalytic degradation efficiencies of DNBP in the presence of PMS were obviously enhanced from 63.62% to 86.85% within 180 min as the concentration of PMS increased from 3 to 6 mmol l −1 . The higher PMS concentration is propitious to generating more active SO 4 •− radicals which could contribute to higher degradation rate of DNBP. Nevertheless, a further increase in PMS concentration had no obvious influence on DNBP degradation efficiency, which could be due to the fact that the generated SO 4 •− radicals could be selfconsumed and captured by excess PMS [48].…”
Section: Catalytic Degradation Of Dnbpmentioning
confidence: 99%
See 2 more Smart Citations
“…The catalytic degradation efficiencies of DNBP in the presence of PMS were obviously enhanced from 63.62% to 86.85% within 180 min as the concentration of PMS increased from 3 to 6 mmol l −1 . The higher PMS concentration is propitious to generating more active SO 4 •− radicals which could contribute to higher degradation rate of DNBP. Nevertheless, a further increase in PMS concentration had no obvious influence on DNBP degradation efficiency, which could be due to the fact that the generated SO 4 •− radicals could be selfconsumed and captured by excess PMS [48].…”
Section: Catalytic Degradation Of Dnbpmentioning
confidence: 99%
“…The dramatical development of industrialization and rapid depletion of resource lead to environmental detrimental aspects to the eco-environment and human beings [1,2]. The widespread and potential risky refractory pollutants, especially water pollution, have triggered worldwide concern for environmentalists and researchers [3,4]. A variety of physical, chemical and biological the-state-of-the-art technologies have been leveraged to address the issues [5], among which adsorption and catalytic oxidation treatment of organic pollutants have intensively investigated and proven to be efficient on wastewater treatment [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of enzymes (β‐lactamases) which effectively deactivate the antibiotics . Hydrolysis of the β‐lactam ring may be also promoted by metal cations . Because of the importance of the process of hydrolysis of the β‐lactam ring this process has been also theoretically studied in detail …”
Section: Introductionmentioning
confidence: 99%
“…In general, there is no ESI‐MS data reported concerning the products of hydrolysis of cephalosporins (to the best of our knowledge). Only in a paper by Chen et al was it mentioned that the product of cephalexin hydrolysis was identified by LC/MS . A number of cephalosporins have been subjected to hydrolysis and the products have been analyzed by ESI‐MS .…”
Section: Introductionmentioning
confidence: 99%